Pan-cancer analysis of STAT3 indicates its potential prognostic value and correlation with immune cell infiltration in prostate cancer - Zhouting Tuo; Hesong Zhang; Ke He; Zhiwei Jiang; Chao Jiang; Xin Chen; Haichao Yuan (Discover Oncology)
Abstract Background Targeting the STAT3 signaling pathway is a promising therapeutic approach for cancer patients. However, the association between STAT3 expression, the tumor immune microenvironment, and genetic variation remains unclear across human cancers, especially prostate cancer. Methods We used R software and other tools to analyze pan-cancer and mutation data from publicly available databases statistically. A comprehensive investigation was performed to assess the genetic heterogeneity and clinical relevance of STAT3 in various malignancies, with a specific focus on its role in the immune landscape and prognostic significance in prostate cancer. The findings were validated through immunohistochemistry (IHC) and multiplex immunofluorescence (mIF). Results STAT3 expression is abnormal in the majority of cancer tissues, which is strongly correlated with these patients' prognosis. Eight measures of tumor heterogeneity and six measures of tumor stemness of multiple tumor types showed a strong correlation with STAT3 expression. Furthermore, in individuals with prostate cancer, STAT3 expression indicated the degree of immune cell infiltration and the advancement of the disease. IHC analysis revealed that STAT3 was down-regulated in prostate tumor tissues, while mIF analysis demonstrated that STAT3 signaling (p-STAT3) was extensively active in tumor tissues and positive lymph node tissues. Conclusion STAT3 may serve as a valuable prognostic biomarker and therapeutic target across various cancers, with particular relevance to prostate cancer.